2008
DOI: 10.1038/ejcn.2008.41
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and impact of sleep duration in children and adolescents: data of the Kiel Obesity Prevention Study

Abstract: Background/Objectives: This study investigates determinants of sleep duration and its impact on nutritional status, resting energy expenditure (REE), cardiometabolic risk factors and hormones in children/adolescents. Subjects/Methods: In 207 girls and 207 boys (13.0±3.4 (6.1-19.9) years) body mass index standard deviation score (BMI SDS), waist circumference (WC) z-score, body composition (air-displacement plethysmography), REE (ventilated hood system; n ¼ 312) and cardiometabolic risk factors/hormones (n ¼ 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
168
9
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(216 citation statements)
references
References 41 publications
14
168
9
13
Order By: Relevance
“…This can be due to a small statistical power or the fact that meal patterns, TV viewing and food habits, which all have been associated with sleep duration (Ray et al, 2007;Hitze et al, 2009;Westerlund et al, 2009) were mediators of this association. In two other studies, sleep duration has been related to larger WC, but mostly only among girls Hitze et al, 2009). In many recent studies, shorter sleep duration has been found to be associated with overweight in children (Patel and Hu, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to a small statistical power or the fact that meal patterns, TV viewing and food habits, which all have been associated with sleep duration (Ray et al, 2007;Hitze et al, 2009;Westerlund et al, 2009) were mediators of this association. In two other studies, sleep duration has been related to larger WC, but mostly only among girls Hitze et al, 2009). In many recent studies, shorter sleep duration has been found to be associated with overweight in children (Patel and Hu, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a TV in a child's bedroom was found to be associated with larger WC and other obesity measures, but only in boys (Delmas et al, 2007). Shorter sleep duration was related to larger WC, at least in girls in two studies Hitze et al, 2009). Only few studies have reported results on food habits and WC in children.…”
Section: Introductionmentioning
confidence: 91%
“…For instance, children with short sleep duration show decreases in leptin concentrations, decreased insulin sensitivity and altered cortisol concentrations, all promoting lipogenesis. 15,51,52 Thus, changes in hypothalamic functioning, such as altered hypocretin-1 signaling may explain the relationship between the changes in BMI and in sleep duration during puberty, via altered puberty onset, energy balance regulation and circadian rhythm. As food-entrainment in addition to light-entrainment, functions as a 'Zeitgeber' of the circadian rhythm, possibly alterations in dietary patterns may also explain the relationship between BMI and sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Na puberdade, pode ser identificado um atraso de fase, caracterizado por horários tardios de dormir e acordar que, somados aos horários sociais e de início das aulas pela manhã, levam a uma importante diminuição das horas de sono [12][13][14] . Por conseguinte, uma duração inadequada de sono está associada a um aumento da sonolência diurna, dificuldades de aprendizagem, diminuição da qualidade de vida e maiores prevalências de doenças como a obesidade 7,15,16 .…”
Section: Artigo Original Introduçãounclassified